If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + -1x = 3x + 2 Reorder the terms: 2 + -1x = 2 + 3x Add '-2' to each side of the equation. 2 + -2 + -1x = 2 + -2 + 3x Combine like terms: 2 + -2 = 0 0 + -1x = 2 + -2 + 3x -1x = 2 + -2 + 3x Combine like terms: 2 + -2 = 0 -1x = 0 + 3x -1x = 3x Solving -1x = 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -1x + -3x = 3x + -3x Combine like terms: -1x + -3x = -4x -4x = 3x + -3x Combine like terms: 3x + -3x = 0 -4x = 0 Divide each side by '-4'. x = 0 Simplifying x = 0
| 3x+1=6-2x | | 4+x=3+0.5x | | 1y+8=7 | | 0.70*x=8000 | | r+23.57=30 | | 20x^2-33x^2-67x-24/5x-3 | | 2(t-3)=4-3t | | 5/4=8/x | | y+17=2y | | 2y+9y=0 | | 5x-1=3(x-7)+4 | | S-8.4=11.3 | | 2=a | | v-6=10+v | | 3y-6=4x-9 | | 22-9x=-5(6x+3)-5(-4-x) | | 4x=15-(-5) | | 9=N/5=19 | | t(squared)=81 | | x^2-2/3=x-1/2-1/6 | | 19-11=x/-8 | | 2x-3+5x+13=29 | | 100=100x+.25 | | 33x+13x=2 | | 0.6x-0.4(50+x)=0.3(50) | | x(squared)=16 | | 4x+2x=0 | | x(t)=2t^4-9t^3+9t^2+t-3 | | x2-2/3=x-1/2-1/6 | | X-1/x-6 | | 2x^3+3=39 | | 9x+2=7x-6 |